Interphotoreceptor Retinoid-Binding Protein (IRBP) in Retinal Health and Disease - Zeng, Shaoxue; Zhang, Ting; Madigan, Michele C.; Fernando, Nilisha; Aggio-Bruce, Riemke; Zhou, Fanfan; Pierce, Matthew; Chen, Yingying; Huang, Lianlin; Natoli, Riccardo; Gillies, Mark C.; Zhu, Ling (Frontiers in Cellular Neuroscience, 2020)
Interphotoreceptor retinoid-binding protein (IRBP), also known as retinol binding protein 3 (RBP3), is a lipophilic glycoprotein specifically secreted by photoreceptors. Enriched in the interphotoreceptor matrix (IPM) and recycled by the retinal pigment epithelium (RPE), IRBP is essential for the vision of all vertebrates as it facilitates the transfer of retinoids in the visual cycle. It also helps to transport lipids between the RPE and photoreceptors. The thiol-dependent antioxidant activity of IRBP maintains the delicate redox balance in the normal retina. Thus, its dysfunction is suspected to play a role in many retinal diseases. We have reviewed here the latest research on IRBP in both retinal health and disease, including the function and regulation of IRBP under retinal stress in both animal models and the human retina. We have also explored the therapeutic potential of targeting IRBP in retinal diseases. Although some technical barriers remain, it is possible that manipulating the expression of IRBP in the retina will rescue or prevent photoreceptor degeneration in many retinal diseases.